A two-dimensional amide-linked covalent organic framework anchored Pd catalyst for Suzuki-Miyaura coupling reaction in the aqueous phase at room temperature. Issue 51 (17th December 2020) - Wu, Shang; Ding, Ning; Jiang, Pengwei; Wu, Lan; Feng, Qiaoliang; Zhao, Lianbiao; Wang, Yanbin; Su, Qiong; Zhang, Hong; Yang, Quanlu
Graphical abstract: Abstract: We have developed an attractive method for Suzuki coupling reaction with good functional-group tolerance under mild conditions. Highlights: A stable covalent organic frameworks anchored palladium catalyst was synthesized. Pd@COF-TM catalyst has been developed highly efficient for Suzuki coupling reaction. The catalyst shows outstanding stability and reusability. Abstract: A two-dimensional amide-linked covalent organic frameworks (2D-COFs) supported Pd catalysis system was synthesized. Fourier transformed Infrared (FTIR), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) are used to characterize the prepared catalyst. Electron microscopes (SEM and TEM) are employed to know the morphologies of the synthesized catalysts. The catalyst is an efficient heterogeneous catalyst for Suzuki-Miyaura coupling reaction, exhibits high catalytic activity for various aryl halides and aryl boronic acids in aqueous media at room temperature. More importantly, the catalyst with high stability could be easily recycled for at least nine runs without decrease of the catalytic activity.